Pengaruh Perendaman Thallus Gracillaria sp. Dalam Media Pupuk Grund Dengan Dosis Berbeda Terhadap Pelepasan dan Penempelan Spora - Salilama, Marlin; Tuiyo, Rully; Mulis; Lideman (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The objective of this study was to explore the effect of thallus Gracillaria sp. immersion in Ground fertilizer with the addition of an Atonic growth regulator on spore release and attachment and to determine the best dose of the Grund fertilizer with the same addition of growth regulator mentioned previously. From April to June, 2021, this research was conducted at Fisheries Center for Brackish Water Aquaculture/BalaiPerikananBudidaya Air Payau (BPBAP) Takalar. Further, it employed an experimental method with a Completely Randomized Design with four treatments and three replications, i.e., Treatment A SWW (Sterile Seawater), B (1% Ground + 0.2 Atonic), C (2% Ground + 0.2 Atonic), and D (3% Ground + 0.2 Atonic). The results of the ANOVA showed that the use of Ground fertilizer + Atonic growth regulator significantly influenced spore release at the significance level of 5% (sig. value < 0.05). Meanwhile, there was no significant difference in spore attachment at the significance level of 5% (sig. value > 0.05). The best dose from the spore release and attachment was in treatment C (2% Ground + 0.2 Atonic). Keywords: Gracilariasp, Ground Media, Atonic Growth Regulator, Spore Release and Attachment.